Temperature-responsive PCL-PLLA nanofibrous tissue engineering scaffolds with memorized porous microstructure recovery - Woodbury, Seth M.; Swanson, W. Benton; Douglas, Lindsey; Niemann, David; Mishina, Yuji (Frontiers in Dental Medicine, 2023)
Biomaterial scaffolds in tissue engineering facilitate tissue regeneration and integration with the host. Poor healing outcomes arise from lack of cell and tissue infiltration, and ill-fitting interfaces between matrices or grafts, resulting in fibrous tissue formation, inflammation, and resorption. Existing tissue engineering scaffolds struggle to recover from deformation to fit irregularly shaped defects encountered in clinical settings without compromising their mechanical properties and favorable internal architecture. This study introduces a synthetic biomaterial scaffold composed of high molecular weight poly (L-lactic acid) (PLLA) and an interpenetrating network of poly (ε-caprolactone) (PCL), in a composition aiming to address the need for conformal fitting synthetic matrices which retain and recover their advantageous morphologies. The scaffold, known as thermosensitive memorized microstructure (TS-MMS), forms nanofibrous materials with memorized microstructures capable of recovery after deformation, including macropores and nanofibers. TS-MMS nanofibers, with 50-500 nm diameters, are formed via thermally induced phase separation (TIPS) of PLLA after in situ polymerization of PCL-diacrylate. A critical partial-melting temperature of TS-MMS at 52°C enables bulk deformation above this temperature, while retaining the nanofibrous and macroporous structures upon cooling to 37°C. Incorporation of drug-loaded poly (lactide-co-glycolide) (PLGA) nanoparticles directly into TS-MMS nanofibers during fabrication allows sustained release of a model drug for up to 40 days. Subcutaneous implantation in vivo using LysM-Cre;td-Tomato;Col1eGFP mice demonstrates successful cellularization and integration of deformed/recovered TS-MMS materials, surpassing the limitations of deformed PLLA scaffolds, to facilitate cell and vasculature infiltration requisite for successful bone regeneration. Additionally we demonstrated a method for embedding controlled release vehicles directly into the scaffold nanofibers; controlled release of simvastatin, enhances vascularization and tissue maturation. TS-MMS scaffolds offer promising improvements in clinical handling and performance compared to existing biomaterial scaffolds.